2019
DOI: 10.1111/btp.12684
|View full text |Cite
|
Sign up to set email alerts
|

Experiments with artificial nests provide evidence for ant community stratification and nest site limitation in a tropical forest

Abstract: Ants are dominant in tropical forests and many species nest in hollow cavities. The manner in which species are vertically stratified in these complex habitats is not known, with lack of nest sites being proposed to limit ant populations. Here, we assess ant community stratification and nest site limitation in a lowland rainforest in New Guinea using experimental addition of artificial bamboo nests of two cavity sizes (small: ~12 mm large: ~32 mm diameter) placed at ground level, in the understorey, and in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 58 publications
0
16
0
1
Order By: Relevance
“…For example Klimes et al (2011) showed that manipulative experiments of arthropods are feasible at the whole‐forest plot level, and Mottl et al . (2020) found that tropical ants were limited by nest site availability (i.e. resource availability) by manipulating artificial nests.…”
Section: Discussionmentioning
confidence: 99%
“…For example Klimes et al (2011) showed that manipulative experiments of arthropods are feasible at the whole‐forest plot level, and Mottl et al . (2020) found that tropical ants were limited by nest site availability (i.e. resource availability) by manipulating artificial nests.…”
Section: Discussionmentioning
confidence: 99%
“…However, in some cases, peripheral zones at different heights in the crown may experience similar wind and sunlight conditions as the top of the tree (Johansson, 1974). This non‐homogeneous distribution of abiotic conditions and resources affects ant foraging (Tanaka et al ., 2010; Yusah & Foster, 2016; Mottl et al ., 2019) depending on the characteristics of the individual species and which vertical strata it occupies, for instance, the understory or canopy (Spicer et al ., 2017). Thus, different ant species are expected to forage in different conditions at the micro‐scale (i.e., in terms of locations within trees and branch characteristics) within the tree crown.…”
Section: Introductionmentioning
confidence: 99%
“…Low colonization percentages also occurred in the same region where Vidal-Hernandez and Armbrecht (2009) found colonization values of 13.24% and 6.03% in artificially added bamboo twigs both in shade-grown and sun-grown coffee, respectively. The percentage of colonization was low compared to other studies (Hosang et al, 2010;Mottl et al 2019), possibly due to a reduction in ant diversity and abundance with elevation (Lach et al, 2010). Although ants are found on almost all continents (except Antarctica), they are mainly found at low latitudes and, in general, there is a monotonal reduction of ant richness with altitude (Fisher, 2010).…”
Section: Discussionmentioning
confidence: 62%
“…Hosang et al (2010) managed to enhance the predator ant Dolichoderus thoracicus using artificial nesting substrates while De la Mora et al (2015) found that prey removal by ants on coffee plantations was positively correlated with hollow coffee twigs. Further, heterogeneous nesting resources (substrates) could be important in promoting ant diversity and abundance (Armbrecht et al 2004;Mottl et al, 2019) Given these studies and the potential of ants as biocontrol agents, an assessment is needed for the type of substrates or the appropriate configurations required to favour ant colonization in a given agroecosystem.…”
Section: Introductionmentioning
confidence: 99%